Parkour-Related Death: Case Report and Review of the Literature. Issue 3 (September 2013) - Back, Jason; Knight, Laura
Closely related to free running, parkour is a running sport that aims to traverse the environment as efficiently as possible, and may involve such stunt-like maneuvers as jumping over urban obstacles like benches, scaling walls, and even jumping from rooftops. We report a case of a young adult aficionado of parkour who suffered a fatal head injury from a short-distance fall while attempting a wall-hop and spinning maneuver in which he missed his grip on a railing. An autopsy was performed at the Medical Examiner's Office, with findings of blunt force trauma of the head. To our knowledge, this is the first case of parkour-related death reported in the medical literature, and we propose that this case may represent a prototype for the pattern of injury (i.e., severe blunt head trauma) that could prove fatal to a practitioner of parkour. Despite the seemingly apparent danger of these stunts, review of the medical literature reveals only a handful of reported cases of parkour-related injury. These injured parkour practitioners tend to be adolescent to young adult males, typically with fractures of the distal extremities (hands, feet, radii, and tibias) and clavicles. Finally, another forensically relevant feature of parkour-related death is the potential for difficulty in determining manner of death, distinguishing accident from suicide or even homicide, depending on the circumstances.